The genus Argiope (Araneae: Araneidae) in The Province of Chiriqui, Panama (Aporte Santiaguino, 2021)
This research presents the species of the genus Argiope Audouin, 1827 (Araneae: Araneidae), found in agricultural and urban areas from Chiriqui, Panama. To do this, since August until November 2020, the locations of David, Alanje, Bugaba, Paso Ancho and Cerro Punta were visited. Random samplings were carried out both in crops and in surrounding vegetation, searching for Argiope specimens, also keeping a photographic record and georeferencing. Arachnids were reviewed in the laboratory for their identification, supported by specialized literature. According to the results, the species Argiope argentata (Fabricius, 1775), was present in the five locations visited; while Argiope trifasciata (Forskal, 1775) was only found in Paso Ancho, Tierras Altas District. Although the genus may be considered cosmopolitan and widely distributed in America, the predominance of A. argentata suggests that it could have a greater capacity for adaptation than A. trifasciata. In conclusion, two species of the genus Argiope are confirmed for the Province of Chiriquí.